Peningkatan Kemampuan Menulis Imla’ Melalui Model Pair Dictation Pada Peserta Didik Kelas VIII MTs Miftahul Jannah Rappolemba Kabupaten Gowa - Fadhil, Andi Ahmad; Chalik, Sitti Aisyah; Dwi Saputri, Fitri Okladis (Shaut al Arabiyyah, 2025)
Abstract: This study aims to evaluate the effectiveness of the Pair Dictation model in improving Imla' writing skills in class VIII students at MTs Miftahul Jannah Rappolemba, Gowa Regency. The study also aims to identify students‘ main difficulties in writing Imla’ and explain how this method can overcome these difficulties. The Pair Dictation model was chosen for its collaborative approach that is able to increase students' active participation in learning. This study used a quasi-experimental method with a pre-test and post-test design. The research subjects consisted of two groups: the experimental group using the Pair Dictation model and the control group using the conventional learning method. Data were collected through Imla‘ writing ability test and analysed using statistical tests as well as effect size analysis to determine the significance of the improvement in students’ writing ability. The results showed that students in the experimental group experienced significant improvement in Imla' writing ability compared to the control group. The effect size analysis (η2=0.75η^2=0.75η2=0.75) shows that this model has a great influence on improving students' skills. Difficulty factors faced by students include lack of basic Arabic knowledge, a more theoretical learning approach, and lack of independent practice.